Students' Experiences Using Chatgpt As A Learning Resource In English Class At SMA Negeri 1 Pematangsiantar - Trinita Ivana Rumapea; sanggam siahaan; Bernieke A.R Damanik (PIJAR: Jurnal Pendidikan dan Pengajaran, 2026)
This study explores the lived experiences of Grade XI students at SMA Negeri 1 Pematangsiantar in using ChatGPT as a learning resource in English writing classes. Using a qualitative phenomenological approach, data were collected from 36 students through open-ended questionnaires, essay writing tasks, and classroom observations. The findings show that ChatGPT improved students' grammar, vocabulary, idea generation, and writing confidence. However, challenges such as over-reliance, stylistic mismatch, and limited internet access were also identified. Students who used ChatGPT critically and reflectively produced better writing than those who relied on it passively. The study concludes that ChatGPT can effectively support EFL writing when accompanied by active student engagement and appropriate teacher guidance.